PENGARUH PENDIDIKAN KESEHATAN TENTANG HIV/AIDS TERHADAP SIKAP GAYA HIDUP BEBAS REMAJA PADA SISWA-SISWI KELAS 11 IPS 3 SMA I KRISTEN SURAKARTA - Ningsih, Endang Dwi; Yankusuma S, Ditya (Intan Husada : Jurnal Ilmiah Keperawatan, 2017)
Background: The poor of HIV/AIDS knowledge to be cause the teens promiscuity. Related to this, the author intends to do a research with a title “ The influence of educating HIV/AIDS health associate with free sex lifestyle attitude toward the teenage students of class 11 IPS 3 SMA I Kristen Surakarta Objective: To determine the influence of educating HIV / AIDS health toward the teenage free sex life style attitude of the students class 11 IPS 3 SMA I Kristen Surakarta. Methods: The quasi-experiments to determine the influence of education HIV / AIDS health associate with the teenagers free lifestyle attitude by using one group pre test and post test that compares the results before and after being given educating HIV/AIDS health. Result: The Paired t test used, the caunting t result is -2, 914 with alpha 5% ( 0,05) obtained the p value of 0,000 < 0,05 it mean Ha accepted and Ho rejected. Conclusion: The educating HIV/AIDS healh influence to the free sex lifestyle attitude of the students of class 11 IPS 3 SMA I Surakarta. Keywords: Educating HIV/AIDS health, Free sex lifestyle attitude teenagers